"Transforming Cross into Crossroads": Afro Carnival Blocos and the Production of Black Spaces in Belo Horizonte - Rezende, Ana Flávia; Silva Saraiva , Luíz Alex; Silva Andrade , Luís Fernando (Organizações & Sociedade, 2024)
In this theoretical essay, we set out to problematize Belo Horizonte from a racial point of view, in terms of processes of domination and resistance, by discussing the production of black spaces through Afro Carnival blocos. We begin with the production of Brazilian cities in relation to the issue of race, highlighting the extent to which this component of the enslavement of blacks and subsequent whitening practices makes cities spaces that are averse to the presence of blacks from the moment of their creation. We then turn to the specificities of Belo Horizonte, the planned capital of Minas Gerais, a symbol of the modernity and progress that was sought in the Brazilian Republic. This debate provides an important backdrop for the discussion of black resistance in the city, which produces spaces of encounter, from a crossroads perspective that can contribute to the spatial turn in Organizational Studies. The main conclusions point to black resistance organizations such as the Angola Janga Afro bloco and Kandandu as a field of possibilities. This recognizes that on the other side of segregation, there are forms of (re)existence of black people, who struggle to be part of this city, while at the same time seeking to strengthen their Afro-diasporic identity and culture. In addition to highlighting their organizational character, these manifestations use aesthetic elements and place black people in a place of (re)existence that signals their right to occupy the city for leisure as well as to produce and reinforce black identities.